Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3390/nano6080153
|View full text |Cite|
|
Sign up to set email alerts
|

Study on Utilization of Carboxyl Group Decorated Carbon Nanotubes and Carbonation Reaction for Improving Strengths and Microstructures of Cement Paste

Abstract: Carbon nanotubes (CNTs) have excellent mechanical properties and can be used to reinforce cement-based materials. On the other hand, the reaction product of carbonation with hydroxides in hydrated cement paste can reduce the porosity of cement-based materials. In this study, a novel method to improve the strength of cement paste was developed through a synergy of carbon nanotubes decorated with carboxyl group and carbonation reactions. The experimental results showed that the carboxyl group (–COOH) of decorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…Through scanning electron microscopy (SEM) observation of a CNT-cement-based material matrix, it was observed that CNTs bridged in the cracks, preventing crack growth and increasing material toughness [17]. CNTs are covered and cemented by cement hydration products in cement-based materials, thus demonstrating the effective mechanical properties of CNTs [18]. CNTs are nanometer in size, enabling them to effectively fill microscopic pores in cement-based materials [15].…”
Section: Introductionmentioning
confidence: 99%
“…Through scanning electron microscopy (SEM) observation of a CNT-cement-based material matrix, it was observed that CNTs bridged in the cracks, preventing crack growth and increasing material toughness [17]. CNTs are covered and cemented by cement hydration products in cement-based materials, thus demonstrating the effective mechanical properties of CNTs [18]. CNTs are nanometer in size, enabling them to effectively fill microscopic pores in cement-based materials [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the fabrication and therapeutic application of CaCO 3 nanoparticles in drug delivery has generated a lot of attention amongst scientists due to its availability, ease of synthesis, low toxicity and slow biodegradability (Mydin et al 2018;Dizaj 2015;Li et al 2019). CaCO 3 nanoparticles have been synthesized using various methods including wet chemical preparation, microemulsion technique and mechanical milling of sea and egg Yan et al 2016) shells (Mydin et al 2018;Dizaj 2015;Ranjan et al 2018). Ghiasi and Malekzadeh (2012) used the sol-gel citrate method to synthesize calcite nanoparticles by adding organic additives as emulsifiers.…”
Section: Calcium Carbonate Nanoparticlesmentioning
confidence: 99%
“…Some of these methods are based on ultrasonication combined with a functionalizing agent, which modifies the CNT surface to ensure a better dispersion [ 23 ]. Amid these methods, the addition of carboxyl groups to the CNT structure must be mentioned, since it boosts hydrophilic features and chemical bonding between CNTs and cement, causing improved adhesion between components [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%